Phenotypic morphology of Bixa arborea and Bixa orellana (Bixaceae) in Alta Floresta, Mato Grosso, Brazil (Research, Society and Development, 2021)
Bixa arborea and Bixa orellana, are two plant species of the Bixaceae family, with wide distribution in South America, and widely used by the traditional population. The species of the genus Bixa have a red to reddish pigment in the seeds, which has been used by native populations for a long time. The phytochemicals present in the seeds of Bixa orellana are also widely used in the food and textile industry (as a dye). Bixa arborea, in addition to the phytotherapic use of leaves, is also widely used in forest restoration and as a source of wood. In this context, it is extremely important to differentiate B. arborea from B. orellana by means of morphological diagnoses to better understand the characters that separate the two species. It also sought to analyze the morphological differences between B. arborea specimens, to assess the existence of hybrids in the analyzed population. For this, morphological diagnoses were carried out for both species. From this, it was possible to notice that the two species have many morphological similarities, differing basically from each other by the aspect of the fruit: B. arborea presented papulous fruits or partially covered by non-flexible spines with length ranging from 0.1-1.8 mm, while B. orellana presents fruits totally covered by flexible spines and with length varying from 4 to 9.6 mm. The average amount of seeds in the fruits of B. orellana was higher than that found in the fruits of B. arborea. Therefore, our work showed that the two species show phenotypic differences, which can be used to identify and differentiate one from the other.